Mapping Me: Mapping Identity among Academically High-Performing Black Males. Issue 6 (June 2016) - Flennaugh, Terry K.
Background: Scholars have argued that far too little research has examined the complex processes that many Black males undertake in constructing identities that function in schools. Some have highlighted the perpetuation of a false dichotomy in which challenges, particularly for Black males, have focused on either individual or institutional culpability. Further, scholarship on Black males that has focused largely on deficits has neglected to include student voice to acknowledge the strategies employed by academically successful Black male students in the face of staggering challenges. The present study investigates academic identity formation with two high-performing Black male students attending an urban high school in Los Angeles, California. Purpose/Objective/Research Question/Focus of Study: Not enough is known about the sense-making process young, academically successful Black males go through in constructing identities that function in school settings. This study explores the complexity of academic self-concept between two academically high-performing Black male high school students through the conceptual and methodological tool of identity mapping. The study explores the following questions: What are the factors that two academically high-performing Black male students identify as being important to their academic self-concept? In what ways, if any, do identity maps provide descriptive information about the construction and performance of academic self-concept among these Black male students? Research Design: Drawing from Multiple Worlds Theory and the work of Cooper, Jackson, Azmitia, Lopez, and Dunbar, and Beach, Lundell, and Jung, this study utilized identity maps to visually represent participants' understanding of multiple aspects of their self-concept through overlapping or disconnected spheres (i.e., multiple worlds). Identity maps were then used as tools for interviews to better understand the academically high-performing Black males' academic self-concept. Findings/Results: Findings suggest that these two academically high-performing Black male students conceptualize their academic identities as socially situated in a myriad of unique ways. Identity maps became an effective tool for both capturing the sense-making process students us to describe highly contextual and complex notions of an academic self and highlighting tensions embedded in the way students identified with schooling. Conclusions/Recommendations: Implications and recommendations for educational researchers and practitioners to make concerted efforts to better understand Black males' identity formation in school settings are discussed.